The impact of lipidome on intervertebral disk degeneration, low back pain, and sciatica: a Mendelian randomization study - Ze-Yu Pang; Yi-Bo Zhu; Jun-Xian Hu; Xiao-Xiao Li; Yong-Jian Gao; Yi-Yang Wang; Qiang Zhou; Pei Li (Scientific Reports)
Abstract Degeneration of intervertebral discs is a significant factor in chronic lower back pain, impacting millions annually. Existing studies propose a potential link between lipids and disc disease, though causal relationships remain unclear. The objective of this study is to explore the causal connections between lipids, lower back pain, disc degeneration, and the risk of sciatica In this research, we utilized a comprehensive GWAS dataset encompassing 179 lipid traits to explore the causal connections between lipids and the susceptibility to conditions such as lower back pain (LBP), intervertebral disc degeneration (IVDD), and sciatica. To establish causality, we employed two-sample Mendelian randomization, supplemented by Bayesian model averaging for verification. Our assessment of diversity and mutual influence involved Cochran’s Q test, MR-Egger intercept assessment, and MR-PRESSO. Additionally, we performed a sensitivity analysis by systematically excluding individual elements to gauge their impact on outcomes in Mendelian randomization. Lastly, bidirectional Mendelian randomization was conducted to explore potential inverse associations between lipids and IVDD. Analyzing 179 lipidomic features as exposures and IVDD, LBP, and sciatica as outcomes, this study reveals significant causal relationships of glycerophospholipids, sterols, and glycerolipids with the risk of IVDD, LBP, and sciatica. Phosphatidylcholine, triglycerides, and sterols consistently exerted risk influences on IVDD, while phosphatidylethanolamine (O-16:1_18:2) among glycerophospholipids exhibited a protective effect (OR: 0.927–0.998, P < 0.05). Regarding LBP, sphingomyelin (d38:2) in sphingolipids demonstrated a protective effect (OR: 0.925–0.997, P < 0.05). For sciatica, triglycerides exhibited a risk influence, with varying effects observed for phosphatidylcholine and sterols with different molecular structures. Notably, sterol ester (27:1/16:1) consistently showed a risk effect across all three conditions. Our research provides valuable insights into how certain lipids are linked to the risks of LBP, IVDD, and sciatica. Our findings indicate that phosphatidylcholine and triglycerides may increase the incidence of IVDD, LBP, and sciatica, suggesting potential adverse effects. In contrast, sphingomyelin appears to reduce the occurrence of LBP and sciatica, indicating a protective role. Sterol esters also show a protective effect against sciatica; however, the sterol ester (27:1/16:1) consistently demonstrates a detrimental impact on IVDD, LBP, and sciatica. Additionally, our study underscores the intricate nature of lipid metabolism concerning IVDD, LBP, and sciatica. It uncovers a range of structural variations among lipids and explores how these variations may lead to different effects across various molecular subtypes.